Single-Incision Laparoscopic Approach, the New Trend in the Minimal Invasive Surgery - An Overview, Current Status and Correlation with Our Experience in Nobel Medical College Teaching Hospital - Sulaimankulov, Ruslan; Jolochieva, Gulmira; Paudel, Bandana (Birat Journal of Health Sciences, 2020)
Introduction: The major purpose of the Minimal Access Surgery is to reduce the number and size of scars, decrease pain and rate of infections, reduce complications, and improve cosmetic effect. In order to achieve scarless surgery there was a development of the Natural Orifice Transluminal Endoscopic Surgery (NOTS), which did not gain popularity and induced growing interest to single-incision laparoscopy as a modern technique with minimal visible scars. Objectives: The objective of this study is to correlate worldwide experience with outcomes of Single-Incision Laparoscopic Surgery (SILS) in our institute. Methodology: A retrospective analysis was done for 9141 patients who underwent Laparo-endoscopic single-site surgery between the year 2011-2020 years (AD). The type of surgery, gender, age, operative time, conversion and complication rate were reported. Results: Laparo-endoscopic single-site surgery was performed for 9141 patients, with a mean age of 46.3 years (range=2.5- 90). Out of 9141 patients included in this study, 8668 patients underwent Cholecystectomy, 232 underwent simultaneous, 161 appendectomy, 54 ovarian cystectomy, 11 underwent myomectomy, 8 diagnostic laparoscopy and 7 cases of salpingo-oophorectomy. The mean operating time was 19.5 minutes (range=4-35 min). In our study complicated cases were 0.996%, conversion done for 0.1% and mortality was 0.02%. Conclusion: The advantages of single access surgery include better cosmetic effect, reduced bleeding, infections, herniations and hospital stay.